PELATIHAN PENYUSUNAN LAPORAN KEUANGAN PERUSAHAAN JASA BAGI SISWA/I SMA NEGERI 2 JAKARTA - Wirianata, Henny; Alberto, Metio; Rusi (Jurnal Serina Abdimas, 2024)
Today's young generation is one of the generations that will be the driving force of the economy in Indonesia in the future. Many young people today have started start-up companies and MSMEs. However, there are still few who have literacy about preparing financial statements. An understanding of financial statements is needed so that when they are starting their business, they can manage their business and their finances properly. Community Service Team from Tarumanagara University (UNTAR) decided to conduct training on how to prepare financial statements for one form of MSMEs, namely a service company for students of SMA Negeri 2 Jakarta. The financial statements to be discussed refer to the MSME Financial Statements as stipulated in the EMKM SAK which consists of income statement, statement of changes in capital, and statement of financial position statements. Training will be carried out offline on Tuesday, March 19, 2024 at 10.00 – 12.00. This activity was attended by students from grades 10 and 11 both from science and social studies majors. Based on the results of the questionnaire, it can be concluded that the training went well as planned. The training participants, students of SMA Negeri 2 Jakarta, gained new knowledge and understood how to prepare financial statements for service companies. This training is expected to improve financial management literacy for SMA Negeri 2 Jakarta students so that they are ready to become business owners and can provide job opportunities in the future. ABSTRAK Para pemuda masa kini merupakan salah satu generasi yang akan menjadi penggerak perekonomian di Indonesia pada masa depan. Banyak generasi muda masa kini yang telah memulai perusahaan start-up dan UMKM. Namun, masih sedikit generasi muda masa kini yang memiliki literasi tentang penyusunan laporan keuangan. Pemahaman tentang laporan keuangan diperlukan agar saat mereka berwirausaha mereka dapat mengelola bisnis dan keuangan usaha mereka dengan benar. Tim PKM Universitas Tarumanagara (UNTAR) memutuskan untuk melakukan kegiatan pelatihan tentang cara penyusunan laporan keuangan untuk salah satu bentuk UMKM yaitu perusahaan jasa bagi siswa-siswi SMA Negeri 2 Jakarta. Laporan keuangan yang akan dibahas mengacu pada Laporan Keuangan UMKM seperti diatur dalam SAK EMKM yang terdiri dari laporan laba rugi, laporan perubahan modal, dan laporan posisi keuangan. Kegiatan pelatihan dilakukan secara luring atau offline pada hari Selasa, 19 Maret 2024 pukul 10.00 – 12.00. Kegiatan ini diikuti oleh oleh siswa/i dari kelas 10 dan 11 baik yang berasal dari jurusan IPA maupun IPS. Berdasarkan hasil kuesioner, dapat disimpulkan bahwa pelatihan berjalan dengan baik sesuai rencana. Peserta pelatihan yaitu siswa/i SMA Negeri 2 Jakarta mendapatkan pengetahuan baru dan memahami cara menyusun laporan keuangan perusahaan jasa. Pelatihan ini diharapkan dapat meningkatkan literasi pengelolaan keuangan bagi para siswa/i SMA Negeri 2 Jakarta agar mereka siap menjadi pemilik usaha dan dapat membuka lapangan pekerjaan di masa depan.